Active LaNi1−xFexO3 bifunctional catalysts for air cathodes in alkaline media1. Issue 18 (14th May 2015) - Zhang, Daiwei; Song, Yufeng; Du, Zhenzhen; Wang, Long; Li, Yutao; Goodenough, John B.
<x xml:space="preserve">Abstract</x> Iron doping in LaNi1−xFexO3 (x = 0, 0.1, 0.2) synthesized by a sol–gel method increases the valence state of the surface Ni and, thereby, the catalytic activity for both the ORR and OER in 0.1 M KOH electrolyte. The Fe-doped LaNiO3 offers a low-cost electrocatalyst for an air cathode in metal–air batteries.